2016
DOI: 10.1038/srep38772
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical ordering in substituted fluorite oxides: a computational investigation of Ho2Zr2O7 and RE2Th2O7 (RE=Ho, Y, Gd, Nd, La)

Abstract: Fluorite-structured oxides find widespread use for applications spanning nuclear energy and waste containment, energy conversion, and sensing. In such applications the host tetravalent cation is often partially substituted by trivalent cations, with an associated formation of charge-compensating oxygen vacancies. The stability and properties of such materials are known to be influenced strongly by chemical ordering of the cations and vacancies, and the nature of such ordering and associated energetics are thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…Pyrochlore oxides have six theoretical Raman active modes [16,[29][30][31][32][33][34][35][36][37] These Raman active modes represent the vibrations of 〈Ln-O〉 and 〈Hf-O〉 bonds [14,[32][33][34][35][36][37][38][39][40]. Raman spectroscopy is more suitable to study anion disorder in pyrochlores as these modes involve motion of oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrochlore oxides have six theoretical Raman active modes [16,[29][30][31][32][33][34][35][36][37] These Raman active modes represent the vibrations of 〈Ln-O〉 and 〈Hf-O〉 bonds [14,[32][33][34][35][36][37][38][39][40]. Raman spectroscopy is more suitable to study anion disorder in pyrochlores as these modes involve motion of oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Shamlin et al showed experimentally that the weberite-like structure, which has a random cationic distribution on the 8c site (7-fold coordinated site), best represents the short-range order in the disordered structure (Shamblin et al, 2016). This has inspired DFT calculations of weberite-type disordered structures (Solomon et al, 2016;Finkeldei et al, 2017;Kowalski, 2020;Matsumoto et al, 2020), which show that disordered fluorite has higher energy than disordered weberite. It is argued that this indicates a possibility of forming weberite-type short-range ordering.…”
Section: Structural Disordermentioning
confidence: 99%
“…This is a curious result as no 2-2-7 chemistries containing +3 and +4 cations have been experimentally reported to have the weberite structure (Cai and Nino, 2009). On the other hand, calorimetry experiments indicate that the short-range order described by weberite is higher in energy than pyrochlore (Solomon et al, 2016;Finkeldei et al, 2017). The discrepancy between experiments and modeling can be explained for some chemistries, namely A 2 Zr 2 O 7 and A 2 Hf 2 O 7 (A Ho, Er, Yb, Lu), which form δ-phase (see Figure 2A), suggesting δ-phase might be preferred and thus should be examined.…”
Section: Structural Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…A recent computational study by Solomon et al shows that low-energy, long-range weberite-type congurations are favored at low values of the ionic radius ratio of A-and B-site cations r A /r B . 48 Random averaging of weberite-type local congurations leads to a long-range disordered, defect uorite structure when averaged over many unit cells. 44,46 Heterogeneous disordering processes with different short-and longrange structural motifs have been similarly observed for other ceramics, such as spinel, 49 and different disordering processes through intrinsic (nonstoichiometry and chemical composition 15,50 ) and extrinsic (ball milling and irradiation 43,51 ) means.…”
Section: Introductionmentioning
confidence: 99%